Sexual and marital satisfaction among married couples: Role of family relationships - Arinze, Nwadiogo C; Olawa, Babatola D (Journal of Psychology and Allied Disciplines, 2024)
The high rate of marital discord and divorce in our present society is quite alarming. Research has shown that marital satisfaction is a precondition for healthy and successful family lives. Hence, to attain a happy and harmonious family living, it is important to investigate the predictors of marital satisfaction. Accordingly, this study examined the influence of sexual satisfaction and family relationships on marital satisfaction and the moderating role of family relationship on the link between sexual satisfaction and marital satisfaction. One hundred and thirty-two convenient samples of married couples in designated areas in Lagos Nigeria, comprising of 67 females and 65 males with a mean age of 37.34years participated in the study. Data collected were analysed using multiple linear regression analysis. Findings suggest that high sexual satisfaction relates significantly with marital satisfaction. Also, a good family relationship has a positive significant relationship with marital satisfaction. More so, the link between sexual satisfaction and marital satisfaction was significantly moderated by family relationship. Results were discussed in line with previous literature, and it was recommended that couples should express affection to each other and not underestimate the importance of sexual and family relationships in commenting their love and ensuring greater marital quality.